2007
DOI: 10.1007/s00299-007-0444-2
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-xL transformed peanut (Arachis hypogaea L.) exhibits paraquat tolerance

Abstract: The human Bcl-xL gene was transformed into peanut cultivar Georgia Green via microprojectile bombardment. Following selection on hygromycin-containing medium and regeneration, eighty hygromycin-resistant callus clusters were recovered. Southern blot analysis of ten fertile lines revealed multiple insertions of the Bcl-xL transgene in most lines. Western blot analysis of primary plants and T1 progenies demonstrated detectable levels of Bcl-xL expression in four transgenic lines. We could not detect Bcl-xL prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…It has been reported that 5 lM of paraquat (methyl viologen dichloride) @ 0.1% of Tween-20 solution could not affect the level of chlorophyll in transgenic plants, while the seeds of transgenic lines did not germinate due to lack of salinity tolerance, when cultured aseptically on medium supplemented with 100 mM NaCl. Transgenic plants expressing resistance to herbicides but not exhibiting tolerance to salinity have been held due to multiple integration of Bcl-xL gene coupled with its deleterious expression (Chu et al, 2008). Peanut plants having bialophos resistance gene (bar) integrated in genomic DNA confirmed resistance @ 500 ppm concentration of the herbicide BASTA (Hoechst) compared with wild type nontransgenic plants (Brar et al, 1994).…”
Section: Salinitymentioning
confidence: 99%
“…It has been reported that 5 lM of paraquat (methyl viologen dichloride) @ 0.1% of Tween-20 solution could not affect the level of chlorophyll in transgenic plants, while the seeds of transgenic lines did not germinate due to lack of salinity tolerance, when cultured aseptically on medium supplemented with 100 mM NaCl. Transgenic plants expressing resistance to herbicides but not exhibiting tolerance to salinity have been held due to multiple integration of Bcl-xL gene coupled with its deleterious expression (Chu et al, 2008). Peanut plants having bialophos resistance gene (bar) integrated in genomic DNA confirmed resistance @ 500 ppm concentration of the herbicide BASTA (Hoechst) compared with wild type nontransgenic plants (Brar et al, 1994).…”
Section: Salinitymentioning
confidence: 99%
“…Transgenic lines demonstrated improved biomass retention in a greenhouse drought tolerance test and an average of 58% yield increase in a two-year field test. Transgenic peanut expressing a human Bcl-xL gene has improved tolerance to paraquat, a bipyridilium herbicide [76]. Fungal resistance in peanut was enhanced by transforming several genes including barley oxlate oxidase [77,78], mustard defensin [60], rice chitinase [79,80] and chloroperoxidase [81].…”
Section: Transgenicsmentioning
confidence: 99%
“…Georgia Green embryogenic callus was bombarded with anti-apoptotic Bcl-xL gene by microprojectile bombardment. Although BclxL protein was detected in four transgenic lines, just one transgenic line (25-4-2a-19) had stable protein expression and showed tolerance to 5µM paraquat (commercial herbicide) (Chu et al, 2008a). Around 0.6% of total population in USA is affected of IgE-mediated allergic reaction following to peanut consumption (Sicherer et al, 2003).…”
Section: Direct Gene Transfermentioning
confidence: 99%
“…NC-7 were transformed by co-bombardment of hph gene and one of two forms of the PStV coat protein genes and both of the transgenic plants showed high level resistance to the homologous virus isolate (Higgins et al, 2004). Transfer of anti-apoptotic genes originated from mammals, nematods or virus into plants is another approach for enhancement of plant resistance against to biotic and abiotic stresses (Chu et al, 2008a). With this aim, peanut cv.…”
Section: Direct Gene Transfermentioning
confidence: 99%